2017
DOI: 10.1038/ncomms14117
|View full text |Cite
|
Sign up to set email alerts
|

Highly active and efficient catalysts for alkoxycarbonylation of alkenes

Abstract: Carbonylation reactions of alkenes constitute the most important industrial processes in homogeneous catalysis. Despite the tremendous progress in this transformation, the development of advanced catalyst systems to improve their activity and widen the range of feedstocks continues to be essential for new practical applications. Herein a palladium catalyst based on 1,2-bis((tert-butyl(pyridin-2-yl)phosphanyl)methyl)benzene L3 (pytbpx) is rationally designed and synthesized. Application of this system allows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 169 publications
(108 citation statements)
references
References 39 publications
2
106
0
Order By: Relevance
“…In this respect, the groups of Monflier and later on Ionescu investigated the recyclability of watersoluble Pd-catalysts. [55][56][57] Furthermore, we demonstrated the superiority of these ligands for selective formic acid decomposition reactions. [51,52] However,i nt his patent the stability of the recycled catalyst is not reported and it is only stated that the catalyst system was "almost exclusively detected in the organic phase".…”
Section: Introductionmentioning
confidence: 96%
“…In this respect, the groups of Monflier and later on Ionescu investigated the recyclability of watersoluble Pd-catalysts. [55][56][57] Furthermore, we demonstrated the superiority of these ligands for selective formic acid decomposition reactions. [51,52] However,i nt his patent the stability of the recycled catalyst is not reported and it is only stated that the catalyst system was "almost exclusively detected in the organic phase".…”
Section: Introductionmentioning
confidence: 96%
“…However, the enzyme that is required for piRNA 3 0 end maturation in vertebrates remained enigmatic. Nishimura et al [1] in this issue of EMBO Reports and two independent studies [2,3] now identified PNLDC1 as the exonuclease that is responsible for piRNA 3 0 end processing and transposon silencing during mouse spermatogenesis. Together, these studies establish PNLDC1 as the piRNA 3 0 end trimmer in mouse.…”
Section: Alfred W Bronkhorst and René F Kettingmentioning
confidence: 99%
“…A review of the literature reveals that the direct carbonyl insertion reactions involve the use of carbon monoxide (CO) as a highly toxic gas and suffer from one or more drawbacks, such as rigorous reaction conditions, high temperature, difficulty in handling of reactants, and limited utility of high pressurized toxic CO gas, precluding their large‐scale industrial applications. To avoid these drawbacks, metal carbonyls, formic acid, acid chloride, silacarboxylic acids, dimethylformamide (DMF), COgen and SilaCOgen, etc.…”
Section: Introductionmentioning
confidence: 99%